The impact of dietary supplementation with astaxanthin on egg quality and growth of long snout seahorse (Hippocampus guttulatus) juveniles - Palma, Jorge (2019)
This study investigated the effect of dietary astaxanthin supplementation on egg quality and juvenile growth of long snout seahorse (Hippocampus guttulatus). Captive breed seahorse broodstock were fed four diets composed of frozen shrimp [Atlantic ditch shrimp, Palaemonetes varians) used as a vector to deliver artificial diets with increasing levels of astaxanthin (0, 75, 100 and 125 mg kg(-1) dry weight)]. The results indicated that the astaxanthin uptake into eggs from the enriched shrimp diets was highly efficient. Females fed unsupplemented astaxanthin diet produced similar-sized eggs with lower concentration of astaxanthin than females fed diets with astaxanthin. The lower concentration of astaxanthin in the eggs was correlated with the production of smaller juveniles in comparison with the juveniles hatched from parents fed supplemented astaxanthin diets. Juvenile growth and survival was limited by their size on release from the male's pouch as at the end of 28-day postparturition juveniles produced with the diet with no astaxanthin were still significantly smaller (P < 0.05) than those produced from parents fed astaxanthin-supplemented diets. These results demonstrate a significant benefit of dietary astaxanthin supplementation in long snout seahorse diets in terms of improved egg quality and juvenile growth and survival.